Efficient separation of tocopherol homologues in vegetable oil by ionic‐liquid‐based countercurrent chromatography using a non‐aqueous biphasic system. Issue 5 (27th December 2019) - Fan, Chen; Li, Nai; Cao, Xueli
Abstract: Tocopherol homologues are important fat‐soluble bioactive compounds with high nutritional value. However, it is of great challenge to separate these homologues because of their high structural similarities. In this work, ionic‐liquid‐based countercurrent chromatography was used for the separation and purification of tocopherol homologues. Conventional countercurrent chromatography and ionic‐liquid‐based countercurrent chromatography solvent systems were evaluated in respect of partition coefficient, separation factor, and stationary phase retention factor to separate these targets. Kind of ionic liquids, amount of ionic liquid, and sample amount were systematically optimized. A novel countercurrent chromatography non‐aqueous biphasic system composed of n ‐hexane‐methanol‐1‐butyl‐3‐methylimidazolium chloride was established. The baseline separation of tocopherol mixtures was obtained in one cycle process. The ionic liquid played a key role in the countercurrent chromatography separation, which resulted in difference of partition behavior of individual tocopherol in the whole system through different hydrogen‐bonding affinity. Finally, n ‐hexane‐methanol‐1‐butyl‐3‐methylimidazolium chloride (5:5:3, v/v) water‐free biphasic system was successfully applied to separate tocopherol homologues from vegetable oil that was not achieved beforehand. This method can be widely employed to separate many similar molecules such as tocotrienols, tocomonoenols, and marine‐derived tocopherol in food samples.